Karakteristik Demografis dan Perilaku Pengelolaan Keuangan Keluarga: Studi pada Pasangan Menikah di Desa Hiliganowo, Kecamatan Telukdalam, Kabupaten Nias Selatan - Sesri Handayani Duha; Maria Magdalena Bate'e; Kurniawan S. Zai; Serniati Zebua (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study was conducted in Hiliganowo Village, Telukdalam District, South Nias Regency. Based on the observed phenomenon, declining family income may influence the characteristics and behavior of both husbands and wives, potentially leading to conflict and disputes within the household. The purpose of this study was to examine the effect of demographic characteristics on family financial management behavior. Data were collected through observation and the distribution of questionnaires to 36 respondents. The data analysis techniques included validity testing, reliability testing, correlation coefficient analysis, coefficient of determination analysis, partial hypothesis testing using the t-test, and simultaneous testing using the F-test. This study employed a quantitative approach, with data processed using SPSS to obtain accurate results.The findings show that, simultaneously, gender (X1), education and financial knowledge (X2), and income level (X3) have an effect on family financial management behavior (Y). This is indicated by the F-count value of 565.532, which is greater than the F-table value of 2.883. Partially, gender (X1) has a significant effect on family financial management behavior (Y), as shown by a significance value of 0.000, which is below 0.05, and a t-count value of 4.447, which is greater than the t-table value of 0.68177. Furthermore, education and financial knowledge (X2) also have a significant effect on family financial management behavior (Y), as indicated by a significance value of 0.000, which is below 0.05, and a t-count value of 7.796, which is greater than the t-table value of 0.68177. Meanwhile, income level (X3) does not have a significant effect on family financial management behavior (Y), as shown by a significance value of 0.117, which is above 0.05, and a t-count value of -1.612, which is lower than the t-table value of 0.68177..